Effectiveness of the Boarding Training Program at the Medan Vocational and Productivity Training Center (BBPVP Medan) - Muhammad Al-Fatih; Nasrul Syakur Chaniago (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to analyze the effectiveness of the boarding training program at the Medan Vocational and Productivity Training Center (BBPVP Medan) in facing global competition and taking advantage of the demographic bonus that Indonesia will obtain. BBPVP Medan is a training process organizer that focuses on developing 3 (three) main competency aspects: skills, knowledge and attitudes, with a certification process to guarantee that training participants are competent to work. This program is designed to produce competent graduates according to industry standards through established procedures. This research uses qualitative methods with a descriptive analysis approach, data collection through participant observation, interviews using purposive sampling techniques, and documentation studies. Data analysis includes reduction, presentation and drawing conclusions. Based on research results, the boarding training program showed positive results in improving various aspects, such as the skills, knowledge and attitudes of the participants. This also has an impact on increasing their capabilities, adaptation, productivity and innovation in facing global challenges. With the program organized by BBPVP Medan, the workforce is equipped with the ability to compete in the industrial world, open up quality job opportunities, as well as improve community welfare and encourage the nation's economic growth.